Diversifying the technological strategies for recovering bioenergy from the two-phase anaerobic digestion of sugarcane vinasse: An integrated techno-economic and environmental approach - Fuess, Lucas Tadeu (2018)
Technical, economic and environmental aspects of implementing two-phase anaerobic digestion (AD), i.e., acidogenic + methanogenic systems, in sugarcane biorefineries for the treatment of vinasse were assessed based on different strategies to using the hydrogen-rich biogas (biogas-H2) generated via acidogenesis. Phase separation greatly enhanced the bioenergy recovered from vinasse AD compared with single-phase systems (methanogenic phase exclusively). The best results for generating electric energy were observed in combined cycle-based power plants that utilized biohythane (10.8 MW + 5.5 MW for the harvest and inter-harvest, respectively), which is the gaseous biofuel from blending biogas-H2 with the methane-rich stream from the methanogenic phase (biogas-CH4). Moreover, the results of this study indicated that scaling up two-phase AD systems is economically feasible for the treatment of sugarcane vinasse (net present value = USD 208.58–219.86 million) because a better or equivalent economic performance was attained compared with single-phase processes. Optimizing the alkalinization of methanogenic reactors strongly affected both the economic and environmental performance of the process, with better results observed with the use of low sodium hydroxide dosages (4 g NaOH kg−1COD). In summary, our results highlighted that two-phase biodigestion may enhance energy production from vinasse by 20–30% without impairing the profitability of the biorefinery and could lead to slight improvements in the environmental performance of the ethanol production chain via the use of an optimized alkalinization strategy.